1985
DOI: 10.1111/j.1399-0039.1985.tb00406.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐A and ‐B (but not ‐C, ‐Bw4, Bw6 or ‐DR antigens) are expressed on purified spermatozoa

Abstract: HLA‐A and ‐B antigens have been found in purified spermatozoa using a double fluorescence cytotoxicity tecnique and specific absorptions. HLA‐C, ‐Bw4, Bw6 and ‐DR antigens have not been found using the same techniques. Controversial results regarding HLA expression on spermatozoa have been presumably obtained because of a lack of both seminal cell purification and an appropriate more accurate cytotixicity technique. The presence of HLA antigens on seminal cells may be of relevance to explain the postulated imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

1986
1986
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…In contrast to our results, several groups of investigators, most recently Rodriguez-Cordoba & Arnaiz- Villena (1985), reported the presence of HLA-class I, class I1 molecules or R2m on human sperm cells. Since conventional HLA-typing sera were employed instead of monoclonal antibodies in these studies, the possibility has to be taken into account that these might react with molecules specified by HLA-linked genes, or even completely unrelated antigens present on sperm.…”
Section: W6132 Hl 22 22contrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, several groups of investigators, most recently Rodriguez-Cordoba & Arnaiz- Villena (1985), reported the presence of HLA-class I, class I1 molecules or R2m on human sperm cells. Since conventional HLA-typing sera were employed instead of monoclonal antibodies in these studies, the possibility has to be taken into account that these might react with molecules specified by HLA-linked genes, or even completely unrelated antigens present on sperm.…”
Section: W6132 Hl 22 22contrasting
confidence: 99%
“…Fellous & Dausset (1970), Kerek & Afzelius (1972), Arnaiz-Villena & Festenstein (1976). Halim et al (1974Halim et al ( , 1982 as well as Rodriguez-Cordoba & Arnaiz-Villena (1985) reported the presence of H-2 or HLA-class I molecules on mouse or human sperm cells, respectively, and several investigators described haploid expression of these polymorphic proteins as well. &-Microglobulin (8,rn) was detected on spermatozoa by Fellous and coworkers (1976) with a xenoantiserum.…”
mentioning
confidence: 99%